Identification of functional residues essential for dehalogenation by the non-stereospecific α-haloalkanoic acid dehalogenase from Rhizobium sp. RC1 - Abdul Hamid, Azzmer Azzar; Tengku Abdul Hamid, Tengku Haziyamin; Abdul Wahab, Roswanira; Huyop, Fahrul Zaman (Wiley-VCH Verlag, 2013)
The non-stereospecific α-haloalkanoic acid dehalogenase DehE from Rhizobium sp. RC1 catalyzes the removal of the halide from α-haloalkanoic acid D,L-stereoisomers and, by doing so, converts them into hydroxyalkanoic acid L,D-stereoisomers, respectively. DehE has been extensively studied to determine its potential to act as a bioremediation agent, but its structure/function relationship has not been characterized. For this study, we explored the functional relevance of several putative active-site amino acids by site-specific mutagenesis. Ten active-site residues were mutated individually, and the dehalogenase activity of each of the 10 resulting mutants in soluble cell lysates against D- and L-2-chloropropionic acid was assessed. Interestingly, the mutants W34 → A, F37 → A, and S188 → A had diminished activity, suggesting that these residues are functionally relevant. Notably, the D189 → N mutant had no activity, which strongly implies that it is a catalytically important residue. Given our data, we propose a dehalogenation mechanism for DehE, which is the same as that suggested for other non-stereospecific α-haloalkanoic acid dehalogenases. To the best of our knowledge, this is the first report detailing a functional aspect for DehE, and our results could help pave the way for the bioengineering of haloalkanoic acid dehalogenases with improved catalytic properties